Multivariate Curve Resolution of p-Coumaric Acid o-Hydroxylation Reaction Mechanism Catalyzed by Tyrosinase - Sirati Sabet, M.; Gheibi, N.; Ahmadi, A. (Asian Journal of Chemistry, 2012)
Multivariate curve resolution is able to extract the number of components involved in a complex spectral feature and attribute the resulting spectra to chemical compounds. The quantification of the individual spectral contributions develop kinetic models for the process with or without a prior knowledge. Data elaboration by multivariate curve resolution was able to explain the kinetics of degradation, giving the pure spectra of the involved species and the respective concentration variation. In this study, p-coumaric acid ortho hydroxylation of mushroom tyrosinase investigated using UV-VIS absorption spectra and chemometric resolution techniques. From the spectra of the reaction between 200 and 600 nm, number of components and their mole fractions in the reaction solution were determined using chemometric resolution technique. After the determination of components, multivariate curve resolution-alternating least square by initial estimates of spectral profiles and proper constraints, was used to resolve the data matrix into pure concentration and spectral profiles. Using chemical rank determination and subspace comparison the chemical species or chemical rank of matrix obtained three. So, there are three species during monophenolase reaction of mushroom tyrosinase.